Orientation-dependent FRET system reveals differences in structures and flexibilities of nicked and gapped DNA duplexes. Issue 11 (23rd March 2017) - Kashida, Hiromu; Kurihara, Ayako; Kawai, Hayato; Asanuma, Hiroyuki
Abstract: Differences in structures and flexibilities of DNA duplexes play important roles on recognition by DNA-binding proteins. We herein describe a novel method for structural analyses of DNA duplexes by using orientation dependence of Förster resonance energy transfer (FRET). We first analyzed canonical B-form duplex and correct structural parameters were obtained. The experimental FRET efficiencies were in excellent agreement with values theoretically calculated by using determined parameters. We then investigated DNA duplexes with nick and gaps, which are key intermediates in DNA repair systems. Effects of gap size on structures and flexibilities were successfully revealed. Since our method is facile and sensitive, it could be widely used to analyze DNA structures containing damages and non-natural molecules.